«Rinnovare continuamente il mondo». Leopardi, Balzac e il potere della moda - Moscardini, Lorenzo (Rivista Internazionale di Studi Leopardiani, 2024)
The purpose of this essay is to show the ambiguity behind the concept of fashion in Leopardi’s and Balzac’s work. To this end, Leopardi’s Dialogo della Moda e della Morte is juxtaposed with Balzac’s Comédie humaine, in particular with the novel Illusions perdues, where the author explores the realm of fashion to transform it into narrative matter.